Development of a Web-based alcohol intervention for university students: Processes and challenges - Hallett, Jonathan; Maycock, Bruce; Kypri, K.; Howat, Peter; McManus, Alexandra (Wiley Blackwell, 2009)
Introduction and Aims. Despite growing evidence of the efficacy of electronic screening and brief interventions for reducing unhealthy alcohol use, there is no published work describing the development of such interventions. We describe the process of developing and implementing an electronic screening and brief intervention in a large university population. Design and Methods. Thematic analysis of seven focus groups, involving a total of 69 students, informed the content and design of THRIVE (Tertiary Health Research Intervention Via Email). Pilot testing was conducted through usability analysis with a further 16 students. A random sample of 13 000 undergraduates was invited to complete screening and hazardous drinkers were randomised to receive Web-based assessment and feedback or screening alone. Participants' use of THRIVE was examined through server log analysis and responses to questions on instrument design/usability during follow-up assessment 6 months later.Results. A total of 7237 students (56% of those invited) completed screening; 2435 (34%) screened positive for unhealthy drinking; 1251 were randomly assigned to receive the intervention; and 1184 served as controls. In total, 99% of participants found THRIVE easy to complete, 76% said it provided personally relevant information and 55% said they would recommend it to a friend with a drinking problem. Thirty per cent sought additional information on support services through the site. Discussion and Conclusions. Key design elements include ease of access (e.g. via an emailed hyperlink), length (<10 min), clear, non-judgmental language, personalised normative feedback and links to appropriate services. The study demonstrates the potential reach of a carefully implemented intervention in a high-risk, non-treatment-seeking population group.